A centralized mailed program with stepped increases of support increases time in compliance with colorectal cancer screening guidelines over 5 years: A randomized trial. Issue 22 (28th July 2017) - Green, Beverly B.; Anderson, Melissa L.; Cook, Andrea J.; Chubak, Jessica; Fuller, Sharon; Meenan, Richard T.; Vernon, Sally W.
Abstract : BACKGROUND: Screening over many years is required to optimize reductions in colorectal cancer (CRC) mortality. However, no prior trials have compared strategies for obtaining long‐term adherence. METHODS: Systems of Support to Increase Colorectal Cancer Screening and Follow‐Up was implemented in an integrated health care organization in Washington State. Between 2008 and 2009, 4675 individuals aged 50 to 74 years were randomized to receive the usual care (UC), which included clinic‐based strategies to increase CRC screening (arm 1), or, in years 1 and 2, mailings with a call‐in number for colonoscopy and mailed fecal tests (arm 2), mailings plus brief telephone assistance (arm 3), or mailings and assistance plus nurse navigation (arm 4). Active‐intervention subjects (those in arms 2, 3, and 4 combined) who were still eligible for CRC screening were randomized to mailings being stopped or continued in years 3 and 5. The time in compliance with CRC screening over 5 years was compared for persons assigned to any intervention and persons assigned to UC. Screening tests contributed time on the basis of national guidelines for screening intervals (fecal tests annually, sigmoidoscopy every 5 years, and colonoscopy every 10 years). RESULTS: All participants contributed data, but they were censored at disenrollment, death, the age of 76 years, or a diagnosis of CRC. Compared with UC participants, intervention participants had 31% more adjusted covered time over 5 years (incidence rate ratio, 1.31; 95% confidence interval, 1.25‐1.37; covered time, 47.5% vs 62.1%). Fecal testing accounted for almost all additional covered time. CONCLUSIONS: In a health care organization with clinic‐based activities to increase CRC screening, a centralized program led to increased CRC screening adherence over 5 years. Longer term data on screening adherence and its impact on CRC outcomes are needed. Cancer 2017;123:4472‐80 . © 2017 American Cancer Society . Abstract : In a health care organization with clinic‐based activities to increase colorectal cancer screening, adding a centralized screening program has led to significant increases in colorectal cancer screening adherence over 5 years and to fewer individuals with no colorectal cancer screening.